Taking Tax Revenues Over Local Governments – Some Legal Problems - Andrzej Borodo (Prawo Budżetowe Państwa i Samorządu)
The power of local government to take over the taxes can lead to conflicts between the local government and another local government (in whose area the property, the building, the plant, the residence and another taxable objects are located). These conflicts are not a matter of relation: the tax authority – the taxpayer. These problems concern the determination which of the local government has the power to take over the tax.